Enhancement Risk Disease Cardiovascular in Children with Hypospadias - Putra, Aulia Wiratama; Prayuda, Yoga Eka; Suherman, Levita Dyah Kartika; Ratu, Tiffani; Cahyono, Ari Harto (PT Inovasi Pratama Internasional, 2023)
Hypospadias is a congenital disorder in boys due to low fetal androgen hormones. Hypospadias is one of the congenital disorders with the highest prevalence. Several studies have revealed the association of hypospadias with cardiovascular disease. There are still very few studies that summarize cardiovascular manifestations in pediatric hypospadias. Therefore, this study was designed to describe the cardiovascular risk in pediatric patients with hypospadias. Method : Journal searches were carried out through several research databases including Google Scholar, PubMed, and Sciencedirect . The keywords used were